The Significance of Teaching Adjectives in Primary Classes - Janasbay-kizi, Shabatova Rabiga (Researchparks Publishing, 2023)
This article talks about the importance of teaching the adjective phrase in the primary grades and its consistency, the specific features of the adjective phrase. Also, it was mentioned about doing exercises for mastering adjective vocabulary.